Addictive use of social media and motivations for social media use among emerging adult university students - Karayiğit, Cebrail; Groter, Aubrey; Thompson, Michael (Journal of Dependence, 2021)
Objective: The purpose of this study was to examine motivations for social media use (social connectedness, entertainment, social recognition, information) and its relationship with the addictive use of social media among emerging adult university students. Method: In this quantitative study, data were collected from emerging adult university students (N = 446) who completed The Bergen Social Media Addiction Scale (BSMAS) and the Scale of Motives for Using Social Networking Sites (SMU-SNS). Results: The findings showed a moderately strong, positive relationship between addictive use of social media and social connectedness and social recognition motivations. The findings also revealed that females and on-campus students more frequently experience the addictive use of social media than males and off-campus students. Conclusion: The findings from this study provided broad support for the notion that there are significant results that it may still be important to explore a further understanding of the link between the addictive use of social media and different motivations for social media use.